Non-Essential Elements and Their Role in Sustainable Agriculture - Nunes da Silva, Marta; Machado, Joana; Osorio, Jazmin; Duarte, Rafael; Santos, Carla S. (Agronomy (Basel), 2022)
Agricultural systems are constantly under environmental pressure, and the continuous rise of the global population requires an increasingly intensification of agronomical productivity. To meet the current global food demand, particularly in depleted ecosystems under adverse climate conditions, the development of novel agronomical practices, which ensure crop productivity while safeguarding minimal impact to the environment, must be encouraged. Since aluminium (Al), cobalt (Co), selenium (Se), silicon (Si) and sodium (Na) are not essential to plant metabolism, their benefits are often neglected or underestimated in agriculture; however, several studies support their advantages in sustainable agriculture when properly employed. The agronomical uses of these elements have been studied in the last decades, delivering important cues for the improvement of food and feed production worldwide due to beneficial effects in plant growth and productivity, nutrient balance, pest and pathogen resistance, water stress management, heavy-metal toxicity alleviation, and postharvest performance. However, their application has not been addressed as part of a holistic conservation strategy that supports the sustainability of agroecosystems. Here, we discuss the potential use of these elements in sustainable agriculture, and the knowledge gaps that hinder their effective integration into agronomical practices, which result in equally profitable applications while supporting environmental sustainability.